THE EFFECT OF PROFITABILITY, BOARD SIZE, AND WOMAN ON BOARDS ON FINANCIAL DISTRESS - Cahyani, Fernanda; Imelda, Elsa; Vira, Vira; Sastrasasmita, Emillia (Graduate Program of Universitas Tarumanagara, 2025)
Financial distress is a condition that often occurs in companies due to internal and external factors. This condition must be addressed immediately because it could endanger the business. This research attempts to collect empirical information about how profitability, board size, and women on board impact firms on the LQ-45 company list that are experiencing financial difficulties. Multiple linear regression is the methodology used in this study. EViews version 12 is used for data processing. In this research, the dependent variable is the level of financial distress which is proxied by the Debt-to-Equity Ratio (DER). According to this study, financial distress is negatively impacted by board size and profitability, positively and significantly by having woman on the board of directors, also completely unaffected by having a woman on the board of commissioners.